Direct methods for stability analysis of electric power systems : theoretical foundation, BCU methodologies, and applications - Chiang, H. (Hsiao-Dong) (Hoboken, N.J. : John Wiley & Sons, 2010)
'Widely accepted around the world, the BCU method is the only direct method used in the power industry. Direct Methods for Stability Analysis of Electric Power Systems presents a comprehensive theoretical foundation of the method and its numerical implementation. This book provides graduate students, researchers, and practitioners with theoretical foundations of direct methods, energy functions, and the BCU method as well as the group-based BCU method and its applications. Numerical studies on industrial models and data are also included'--
'This book describes the BCU method (Boundary of Stability Region Based Controlling Unstable Equilibrium Point method)'--
Includes bibliographical references and index.
Keywords: Electric power system stability; Boundary element methods; Electric power systems -- Mathematical models